Does Bone Mineral Density Have an Affect on the Visual Analogue Scale Pain Score? - Kenan Özler (Galenos Yayinevi, 2020)
Objective:The objective of this study is to evaluate the Visual Analogue scale (VAS) pain scale in elderly patients with obesity and without obesity, and determine whether the VAS pain score is associated with obesity in patients with osteoporosis.Materials and Methods:We included 192 patients in this study (69 patients with body mass index (BMI) <30 and 99 patients with BMI ≥30). We determined the values of bone mineral density (BMD) by the dual-energy X-ray absorptiometry method. Importantly, we evaluated the VAS pain scores in the range of "without pain" (score=0) and "the worst pain" (score=10), and divided them into three groups according to the World Health Organization's pain severity scale: mild pain (score: <3), mild-moderate pain (score: 3-6), and moderate-severe pain (score: >6). Additionally, we used a multivariate logistic regression model to identify the independent risk factors of VAS pain score in patients with osteoporosis.Results:The VAS pain score was higher in patients with obesity than the patients without obesity (4.49±2.76 and 3.49±.42, respectively. P=0.014). Advanced age [Odds ratio (OR)=1.094, 95% confidence interval (CI)=1.018-1.175, p=0.014] and obesity (OR=0.225, 95% CI=0.055-0.928, p=0.039) were associated with higher VAS pain score in patients with osteoporosis. Otherwise, only advanced age (OR=1.157, 95% CI=1.045-1.280, p=0.005) was associated with higher VAS pain score in patients with normal BMD. Advanced age (OR=1.141, 95% CI=1.093-1.192, p=<0.001) and osteoporosis (OR=0.001, 95% CI=0.00-0.014, p=<0.001) were associated with higher VAS pain score in all patients.Conclusion:We believe that reducing obesity, which is a variable risk factor, will benefit in pain reduction and sedentary lifestyle, and improve BMD in patients with osteoporosis.